2017
DOI: 10.18553/jmcp.2017.23.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Positive Medication Changes Resulting from Comprehensive and Noncomprehensive Medication Reviews in a Medicare Part D Population

Abstract: No outside funding supported this study. The University of Arizona Medication Management Center (UAMMC)/SinfoniaRx provides grant funding to the University of Arizona for research. Augustine reports support from the UAMMC and ownership of Pfizer stock and was a graduate student at the University of Arizona College of Pharmacy at the time of this study. The authors report no other potential conflicts of interest. Buhl and Augustine contributed study concept and design, collected the data, and wrote the manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In this study, Medicare beneficiaries were predominantly female (66%), between the ages of 75 and 84 years (43%), and located in the southern geographic region (42%) of the United States and mostly lived in zip codes where less than 10% of the population was below the FPL (46%). These patients used a median of 14 unique chronic medications (interquartile range: [11][12][13][14][15][16][17]. Complete demographic information is available in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Medicare beneficiaries were predominantly female (66%), between the ages of 75 and 84 years (43%), and located in the southern geographic region (42%) of the United States and mostly lived in zip codes where less than 10% of the population was below the FPL (46%). These patients used a median of 14 unique chronic medications (interquartile range: [11][12][13][14][15][16][17]. Complete demographic information is available in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research described the success of targeted approaches in reducing use of PIMs among older adults. 10,11,[13][14][15][16][17] Automated alerts targeting PIM use in an inpatient setting, paired with a pharmacist-physician collaboration, reduced use of these medications among patients with dementia. 17 The current study adds to the literature by showing that automated TMRs utilizing prescription claims reduce use of potentially harmful medications among Medicare enrolled MTM-eligible patients with dementia served by a national MTM provider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two MTM intervention studies have evaluated completion rates, while other outcomes include total number of claims, pharmacist interventions, and revenue. 13,[19][20][21] This study was the first to determine the effect of a technician-driven MTM program with a novel protocol on a pharmacy chain's EQuIPP scores. MTM vendors identify patients with the same medicationrelated issues monitored on the EQuIPP platform.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the per patient recommendations far surpassed those reported by others. 14,19 Buhl et al (2017) reported 0.809 and 0.818 recommendations per patient per year for those participating in pharmacist-delivered CMRs over a 2-year period, respectively. Also, Buhl et al only noted medication additions or deletions rather than total recommendations per patient, so it is possible that the interventions were underreported.…”
Section: Demographic Characteristics Of Study Participants (N = 86)mentioning
confidence: 99%